Specificity of Immunoglobulin Response to Nontuberculous Mycobacteria Infection in People with Cystic Fibrosis - Kenneth C. Malcolm; Emily A. Wheeler; Kara Calhoun; Patricia M. Lenhart-Pendergrass; Noel Rysavy; Katie R. Poch; Silvia M. Caceres; Milene T. Saavedra; Jerry A. Nick (Microbiology Spectrum, 2022)
ABSTRACT Nontuberculous mycobacteria (NTM) infections are increasingly prevalent in chronic lung diseases, including cystic fibrosis (CF). Mycobacterium abscessus is of particular concern due to relatively greater virulence and intrinsic antimicrobial resistance. Airway culture identification, the standard method for detecting pulmonary infection, is hindered by low sensitivity, long culture times, and reliance on sputum production or lavage. A culture-independent test for detecting NTM infection could complement, or replace, sputum culture, which is becoming more difficult to obtain with reduced sputum production by people with CF (pwCF) on highly effective modulator therapy. We describe an assay for the detection of plasma anti-M. abscessus antibodies of pwCF to antigens from M. abscessus lysates. Anti-M. abscessus IgG and IgA, but not IgM, discriminated with high specificity subjects infected with M. abscessus from those infected by M. avium complex, and from those with distant or no NTM infections. The IgG3 subclass predominated with minor contributions by other subclasses. Both aqueous and organic soluble antigens were recognized by plasma IgG. A validation cohort measuring IgG and IgG3 identified M. abscessus positive subjects, and elevated IgG was sustained over several years. These studies show the benefit of M. abscessus cell lysates to detect plasma IgG of subjects with CF and M. abscessus infections. Subclass analysis suggests that IgG3 is the predominant subtype in these subjects with chronic bacterial infections suggesting a defect in class maturation. Serodiagnosis could be useful to monitor M. abscessus group infections in chronic lung disease as an adjunct or alternative to culture. IMPORTANCE Lung infections with nontuberculous mycobacteria (NTM), and particularly Mycobacterium abscessus, a pathogen with high antibiotic resistance, are of great concern due to poor clinical outcomes and challenging detection in people with cystic fibrosis and other diseases. Standard detection methods are insensitive and increasingly difficult. We describe the measurement of NTM-specific antibodies from plasma to identify subjects infected with M. abscessus. The assay is sensitive and provides information on the immune response to NTM infections. This assay could be used to help identify subjects with NTM pulmonary infections and track disease progression, either alone or in conjunction with other tests.